Three-Dimensional Static Animation of Computation-Intensive 3D-Algorithms - Baker, A.A.; Kappes, S. (2008 International Conference on Computer Science and Software Engineering : 12-14 December 2008, 2008)
The increasing interest and acceptance of algorithm visualisation systems (AVS) has led - by students as well as by lecturers - to an intensified use of those systems in teaching as modern e-learning instruments in the last few years. While a two-dimensional visualization of many algorithms is for didactic reasons completely sufficient there are numerous existing algorithms, particularly in the fields of computer graphics and bioinformatics, whose essential / fundamental properties gain recognition in a three-dimensional visualization. Apparently every noncomputational-intensive algorithm can be visually simulated by using a high-level programming language. However,due to the enormous execution time required to simulate an computational-intensive or an NP-complete algorithm,such kind of algorithms can only be statically animated- either by using an algorithm animation language or even a high-level programming language. In this work we pay special attention to the three-dimensional static animation of NP-complete algorithms and computational intensive 3D-algorithms in the fields of computer graphics and bioinformatics. As almost all currently existing algorithm animation languages are restricted to the two dimensional visualization of conventional algorithms and data structures there is a strong need to develop a new animation language that can be used for the visualization of3D-algorithms.